Efektivitas Media Pembelajaran Berbasis Educaplay dalam Meningkatkan Minat dan Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Rozinah, Siti; Abd. Rahman, M.; Hafidzah, Laily; Ariffudin Hilmi, Ahmad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study aims to determine the effectiveness of Educaplay-based learning media in improving students’ learning interest and classroom participation in Islamic Religious Education and Character Building (PAI) for Grade VIII students at SMP Negeri 225 West Jakarta. Educaplay is a web-based educational gaming platform that provides various interactive activities, such as quizzes, puzzles, video quizzes, and word games, which can be utilized as innovative learning media. This study employed a Classroom Action Research (CAR) design with a qualitative approach supported by quantitative data and was conducted in two cycles. The research subjects consisted of 35 students from Class VIII C at SMP Negeri 225 West Jakarta. Data were collected through observation, interviews, questionnaires, and documentation. The findings indicate that the gradual and structured implementation of Educaplay significantly enhanced students’ learning interest and participation. In the initial condition, only 17.1% of students demonstrated a high level of learning interest, while 14.3% were categorized as highly active participants. Following the implementation of actions in Cycles I and II, the percentage of students with high learning interest increased to 68.6%, while high learning participation reached 71.4%. These findings suggest that Educaplay is effective in creating an interactive and enjoyable learning environment and in encouraging active student engagement in Islamic Religious Education learning.